Arbitrase Internasional: Evaluasi Efektivitasnya sebagai Mekanisme Penyelesaian Sengketa Alternatif - Rudi Natamiharja; Oksha Dwi Anugrah Panjaitan; Ikhsan Setiawan (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2025)
Purpose: This paper aims to determine the extent to which international arbitration is of interest to the parties and how international arbitration can become an adequate alternative settlement. Methodology: This paper is included in the normative research type. The author uses an Analytical Approach. The data collection method in this paper is a literature study. After collecting all the necessary data, the next step is identifying and classifying the data. This research uses a qualitative analysis method. The qualitative analysis method analyzes secondary data that has been obtained to develop hypotheses to answer the problems in this paper coherently and logically. Results: International Arbitration interests the parties due to the advantages of arbitration, one of which is its unlimited relative competence; whether international arbitration is compelling depends on the interests of the parties in the dispute and whether they are fulfilled. Limitations: This research is within the scope of international law. Contribution: This study contributes to understanding the strengths and weaknesses of international arbitration as an alternative dispute resolution mechanism and provides practical recommendations for strengthening domestic and international legal frameworks to enhance its effectiveness